Combined blockade of GPX4 and activated EGFR/HER3 bypass pathways inhibits the development of ALK‐inhibitor‐induced tolerant persister cells in ALK‐fusion‐positive lung cancer - Koh Furugaki; Takaaki Fujimura; Narumi Sakaguchi; Yasutaka Watanabe; Ken Uchibori; Eisaku Miyauchi; Hidetoshi Hayashi; Ryohei Katayama; Shigeki Yoshiura (Molecular Oncology)
Cancers can develop resistance to treatment with ALK tyrosine kinase inhibitors (ALK‐TKIs) via emergence of a subpopulation of drug‐tolerant persister (DTP) cells that can survive initial drug treatment long enough to acquire genetic aberrations. DTP cells are thus a potential therapeutic target. We generated alectinib‐induced DTP cells from a patient‐derived ALK+ non‐small‐cell lung cancer (NSCLC) cell line and screened 3114 agents in the anticancer compounds library (TargetMol). We identified phospholipid hydroperoxide glutathione peroxidase GPX4 as being involved in promoting the survival of DTP cells. GPX4 was found to be upregulated in DTP cells and to promote cell survival by suppressing reactive oxygen species (ROS) accumulation; GPX4 inhibitors blocked this upregulation and facilitated ROS‐mediated cell death. Activated bypass signals involving epidermal growth factor receptor (EGFR)/receptor tyrosine‐protein kinase erbB‐3 (HER3) were also identified in DTP cells, and co‐treatment with EGFR‐TKI plus ALK‐TKI enhanced ROS levels. Triple combination with an ALK‐TKI plus a bypass pathway inhibitor plus a GPX4 inhibitor suppressed cell growth and induced intracellular ROS accumulation more greatly than did treatment with each agent alone. The combined inhibition of ALK plus inhibition of activated bypass signals plus inhibition of GPX4 may be a potent therapeutic strategy for patients with ALK+ NSCLC to prevent the development of resistance to ALK‐TKIs and lead to tumor eradication.